2017
DOI: 10.15184/aqy.2017.25
|View full text |Cite
|
Sign up to set email alerts
|

Satellite imagery and heritage damage in Egypt: a response to Parcak et al. (2016)

Abstract: In a recent article, Parcak et al. (2016) presented the results of a study in which they used satellite imagery to evaluate looting and other damage at over one thousand heritage sites in Egypt. Assessing imagery dating between 2002 and 2013, their results indicated an increase in visible damage to sites during this period caused by looting and encroachment, which by Parcak et al.’s definition “includes building development, cemetery growth, agricultural expansion and intentional damage through targeted destru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 8 publications
1
15
0
Order By: Relevance
“…These satellites also provide an important resource for monitoring in areas of conflict or rapid development. Recent articles by Parcak et al (2016) and Fradley and Sheldrick (2017) in Antiquity, while in disagreement on some points, highlight the importance of ongoing monitoring and timely data updates to manage heritage in dynamic contexts. Several major efforts now leverage the advantages of serial satellite imaging across the Middle East and North Africa for the purpose of site and landscape monitoring, including the Endangered Archaeology of the Middle East and North Africa project (EAMENA - Bewley et al 2016), the ASOR Cultural Heritage Initiatives (Casana and Panahipour 2014;Casana 2015;Danti et al 2017) and the Afghan Heritage Mapping Project (Stein 2015).…”
Section: High Temporal Revisit Satellitesmentioning
confidence: 99%
“…These satellites also provide an important resource for monitoring in areas of conflict or rapid development. Recent articles by Parcak et al (2016) and Fradley and Sheldrick (2017) in Antiquity, while in disagreement on some points, highlight the importance of ongoing monitoring and timely data updates to manage heritage in dynamic contexts. Several major efforts now leverage the advantages of serial satellite imaging across the Middle East and North Africa for the purpose of site and landscape monitoring, including the Endangered Archaeology of the Middle East and North Africa project (EAMENA - Bewley et al 2016), the ASOR Cultural Heritage Initiatives (Casana and Panahipour 2014;Casana 2015;Danti et al 2017) and the Afghan Heritage Mapping Project (Stein 2015).…”
Section: High Temporal Revisit Satellitesmentioning
confidence: 99%
“…As our work progresses, we will need to remain critically aware of the implications for researchers of utilising such a large, standardised dataset [53]. Care must be taken to avoid misleading interpolations (e.g., see Fradley and Sheldrick's [56] commentary on Parcak [57]). For example, statistical variations in site density will need to take into account differential preservation levels which depend on landscape contexts.…”
Section: Resultsmentioning
confidence: 99%
“…Recent debates arising from satellite-imagery assessments of the preservation of thousands of archaeological sites in Egypt have revealed that looting is only a pressing preservation problem in the Nile River Valley and in the Nile Delta, although "encroachment," or the unregulated expansion of human activities, damages the greatest total area of archaeological sites. Broader assessments of a greater variety of types of archaeological sites throughout the Eastern Desert indicate that development and "encroachment" cause much more severe and widespread destruction [64,89,90].…”
Section: Discussionmentioning
confidence: 99%